Combating violence against women in federal and Kurdistan legislation - ALNomani, Maitham Mohammad Abd; Jawad, Aseel Hafedh (Journal of Legal and Political Studies, 2025)
Since ancient times, women have suffered from violence, which is a global phenomenon that has swept across all Western and Arab societies. It is also a crime committed by saying or doing something or threatening to do something that would affect the psychology and emotions of women, who represent half of society, as mothers, wives, sisters, or daughters. Thus, it exposes the security of the family to danger, which in turn threatens the entity of the state and society, respectively. Although the legal legislations addressed the issue of violence against women, this treatment was incomplete, especially since abused women are exposed, in light of the silence of society, to a great danger that needs to be highlighted, with the aim of addressing the deficiency in the Iraqi federal legislation in general and in the Kurdistan legislation in particular; in order to highlight the concept of the crime of violence against women, which requires adding new texts or making amendments to what is present in them in order to close any legal loophole. Keywords: Violence, women, federal legislation, Kurdistan legislation
Keywords: Violence; women; federal legislation; Kurdistan legislation